Mapping the social aspect of GSCM and SSCM: a future research agenda proposal - Delgado, Fernanda Martinez; de Aragão, Claudia Gomes; Teixeira, Adriano Alves; Bezerra, Barbara Stolte (Revista Gestão da Produção Operações e Sistemas, 2023)
Purpose – Identify how the social dimension is investigated in GSCM and SSCM research and propose a research agenda to integrate the social dimension in GSCM and SSCM. Theoretical framework – The study deals with the social aspect of the triple bottom line, a theory devised by John Elkington, to identify how the topic is treated in GSCM AND SSCM research. Design/methodology/approach – This study adopted a systematic review of the literature approach to examine the literature that integrates GSCM and the SSCM with a focus on the social aspect, based on criteria and an analysis of published studies adapted from Tranfield et al. (2003). Findings - The study contains a summary of the papers found and a categorization that defines the state-of-the-art approach to the subject. The analysis supports the fact that China, India, and European countries carry out most of the investigation and produce GSCM and SSCM articles, observing the social aspect in their releases. Quantitative studies explore sustainability in the economic, environmental, and social tripod together. Research in social performance is not yet specialized and measuring this type of performance in an organization is very complex. Studies that address social issues are scarce, and there are still many gaps to be filled in the investigation of the social dimension in GSCM and SSCM. Research, Practical & Social implications – As theoretical implications, the study presents a delimitation of the state-of-the-art approach on social issues when GSCM AND SSCM themes are worked together. For practical and managerial implications, it serves as a guide for consulting the best social practices to be adopted by companies. Originality/value – The study works on the social aspect between GSCM and SSCM themes together, and studies that deal with social issues are scarce, contributing to the business management area. Keywords - GSCM, SSCM, Sustainability, Social performance, Social issues, Social aspects.